(untitled) (Web of Teachers: Inderscience Research, 2023)
The article highlights the issues of historical impartiality, which is one of the important factors in the formation of the world view of young people, of educating our young people based on our historical values, and protecting them from various influences. Also, attention is paid to a number of problems that require clarification in front of the science of history.